1964
DOI: 10.1111/j.1570-7458.1964.tb02429.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF AN ALTERNATIVE FOOD SUPPLY ON THE RELATIONSHIP BETWEEN TWO TYPHLODROMUS SPECIES AND PANONYCHUS ULMI (KOCH) (ACARINA)

Abstract: Using seedling plants in an insectary, populations were recorded of two species of Typhlodromus (Phytoseiidae) when provided with known numbers of Panonychus ulmi (Koch) (Tetranychidae) and/or large numbers of Aculus fockeui (Nal.) (Eriophyidae). T. pyri Scheut. and T. finlandicus (Oudms.) both maintained P. ulmi at a low level compared with populations where Typhlodromus was not present, and whether or not A. fockeui was also available. Both species of Typhlodromus increased more rapidly when provided with A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

1970
1970
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 2 publications
(2 reference statements)
1
22
0
Order By: Relevance
“…Various researchers have shown that addition of non-prey food for predators can result in improved control of pests (Collyer 1964;Karban et al 1994;Hanna et al 1997;Walde et al 1997;Liu et al 2006). The mechanism causing this is similar to that of apparent competition; the addition of non-prey food results in an increase of predator numbers, which results in a decrease of pest densities.…”
Section: Introductionmentioning
confidence: 94%
“…Various researchers have shown that addition of non-prey food for predators can result in improved control of pests (Collyer 1964;Karban et al 1994;Hanna et al 1997;Walde et al 1997;Liu et al 2006). The mechanism causing this is similar to that of apparent competition; the addition of non-prey food results in an increase of predator numbers, which results in a decrease of pest densities.…”
Section: Introductionmentioning
confidence: 94%
“…In the latter case, predator satiation results in a short-term positive indirect interaction between its prey species. With respect to biological control, some studies have indeed demonstrated that the control of a pest species can be improved by the presence of another pest species (Collyer 1964;Karban et al 1994;Liu et al 2006;Messelink et al 2008), whereas disruption of biological control through predator satiation in the shortterm has also been demonstrated (Koss and Snyder 2005;Symondson et al 2006). So far, both theory and experiments on the effects of a shared predator have ignored the effects of a mixed diet on predator populations.…”
Section: Introductionmentioning
confidence: 99%
“…A.finlandicus is considered to be an important predator of European red mite (Panonychus ulmi) (Koch) (Acari: Tetranychidae) and rust mites (Acari: Eriophyidae) on apple (Malus Xdomestica Borkh.) (Collyer, 1958(Collyer, , 1964van de Vrie, 1975;Genini etal., 1983;Sechser et al, 1984;Schausberger, 1991). This species is a polyphagous facultative predator that can also feed on pollen, honeydew, fungal spores (KropczynskaLinkiewicz, 1971), thrips larvae (Schausberger, 1990) and tyroglyphid and tarsonemid mites (Karg et al, 1987).…”
Section: Introductionmentioning
confidence: 96%